Modification of Cellulose with 4.4 Diaminodiphenylether-O-Hydroxibenzaldehide as Adsorbent and Its Application for Adsorbing Metalic Ion of Cd2+ In Aqueous Solution - Nurlisa HIdayati; Risfidian Mohadi; Euis Marsitho; Ahmad Fatoni (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
This research on the modification of cellulose using 4,4-diaminodiphenylether and o-hydroxybenzaldehyde and its application to adsorb Cd2+ in aqueous solution has been done. The adsorption studies of cellulose and modified cellulose were done by using batch technique. The cellulose and modified cellulose were characterized by FTIR. The FTIR spectra revealed characteristic bands of 1573 cm-1, 1280 cm-1, 3749 cm-1 and 1056 cm-1. It indicates function group of C=N, C=O, O-H and Si-OR bond, respectively. The FTIR spectra of cellulose and modified cellulose which interacted to Cd2+, it were indicated by the shift in wavenumber 3410 cm-1 to 3371 cm-1. This spectral shift indicating Cd2+ bound to OH-group. In this research, interaction between modified cellulose with Cd2+ confirmed by intensities spectral changes at 1620 cm-1. The adsorption capacity and energy from adsorption of Cd2+ ions toward cellulose were 71,43 mg/g and 4,142 kJ/mol, while toward modified cellulose were 55,56 mg/g and 0,13 kJ/mol, respectively. Keywords: cellulose, 4,4-diaminodiphenylether-o-hydroxybenzaldehyde, adsorption, Cd2+